2023
DOI: 10.1097/rlu.0000000000004646
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Detection Performance Between Multiparametric Magnetic Resonance Imaging and Prostate-Specific Membrane Antigen PET/CT in Patients With Localized Prostate Cancer

Abstract: PurposeMultiparametric MRI (mpMRI) has been promoted as an auxiliary diagnostic tool for prostate biopsy. However, prostate-specific membrane antigen (PSMA) including 68Ga-PSMA-11, 18F-DCFPyL, and 18F-PSMA-1007 applied PET/CT imaging was an emerging diagnostic tool in prostate cancer patients for staging or posttreatment follow-up, even early detecting. Many studies have used PSMA PET for comparison with mpMRI to test the diagnostic ability for early prostate cancer. Unfortunately, these studies have shown con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
(824 reference statements)
0
1
0
Order By: Relevance
“…At present, the cost is about 150 dollars, which is about one tenth of the cost of PSMA PET/CT examination. Meanwhile, the meta-analysis found that mpMRI is comparable to PSMA PET/CT in terms of prostate tumor localization and staging detection performance ( 22 ). The multi-modal image fusion targeted transperineal prostate biopsy based on mpMRI mainly includes mpMRI-TRUS cognitive fusion, in-bore fusion and AI software fusion.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the cost is about 150 dollars, which is about one tenth of the cost of PSMA PET/CT examination. Meanwhile, the meta-analysis found that mpMRI is comparable to PSMA PET/CT in terms of prostate tumor localization and staging detection performance ( 22 ). The multi-modal image fusion targeted transperineal prostate biopsy based on mpMRI mainly includes mpMRI-TRUS cognitive fusion, in-bore fusion and AI software fusion.…”
Section: Discussionmentioning
confidence: 99%